Photo-induced activity of BiFeO3/TiO2 nanotube arrays derived from ultrasound-assisted successive ionic layer adsorption and reaction - Zhao, Q.; Ren, Y.; Li, Xin Yong; Shi, Y. (Pergamon, 2016)
© 2016 Elsevier LtdIn this work, a facile strategy of ultrasound-assisted successive ionic layer adsorption and reaction was successfully employed to modify TiO2 nanotube arrays with BiFeO3 nanoparticles. An enhanced positive surface photovoltage was observed with the obtained BiFeO3/TiO2 nanotube arrays as well as a longer lifetime of charges separation state, as probed by transient photovoltage technique. The higher photocurrent density produced by BiFeO3/TiO2 nanotube arrays further indicated that BiFeO3 nanoparticles contributed to photo conversion and promoted the generation of photo-induced charge carriers over TiO2 nanotube arrays. Besides, the prepared BiFeO3/TiO2 electrode exhibited a much enhanced photoelectrocatalytic performance in removing methyl blue compared with bare TiO2 nanotube arrays.